Development of a Community-Based Early Warning System (EWS) Model For Stunting Prevention in Nutritional Status Among Children Under Five Years - Hastuti, Apriyani Puji; Wahyusari, Shinta; Servitia, Aldila Eka (Chakra Brahmanda Lentera Institute, 2025)
Background: Stunting is one of the problems in the context of the triple burden of disease. Growth conditions below standard indicate growth obstacles in the child. This research aims to analyse the factors that influence EWS and to evaluate the application of the EWS model in improving nutritional status in toddlers. The purpose of the study is to develop an EWS for nutritional status in children. Methods: This research used an explanatory design to determine EWS; quasi-experimental sampling was randomised (multistage random design) with 180 respondents in stage 1 and 38 respondents in stage 2—inclusion criteria: mothers who have children and are raising their own child. The research was conducted in the public health sector of Malang Regency. Data collection will be done using a questionnaire for each variable. Data analyzed with Partial Least Square, Wilcoxon Signed Rank Test, and Mann Whitney The results of this study showed that determining factors of EWS were body weight (X1.3), height (X1.4), birth length (X1.6), history of infection (X1.7), minimal weight gain (X1. 11), participation in integrated health service (X2.2), history of maternal infection (X3.2), birth interval (X3.3), land use (X4.2), food hygiene (X5.2), complementary feeding (X6. 1), responsive feeding (X6.2).. Results: The EWS model's effectiveness is associated with minimal weight gain in children (ρ<0.001), but not with nutritional status (ρ=1.000) or upper arm circumference (ρ=0.207). Conclusion: It is hoped that the development of this model can be an intervention with an integrated approach to improve the minimal weight gain which in the long term may enhance nutritional status.of children under five.